PEMERIKSAAN TEKANAN DARAH, INDEKS MASSA TUBUH, GULA DARAH SEWAKTU, DAN KOLESTEROL TOTAL PADA MASYARAKAT DESA DEMULIH USIA DEWASA DAN TUA - I Wayan Sugiritama (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The prevalence of cardiovascular disease is an increase continuously in Indonesia, and as one of the leading causes of death. Several risk factors for cardiovascular disease are overweight, obesity, hypertension, dyslipidemia, and diabetes Mellitus. These risk factors are not only experienced by the urban community but also who live in rural areas. The purpose of this activity is to identify the risk factors of cardiovascular disease in adults and the elderly in the Demulih village. The risk factor data were collected by measuring blood pressure, body mass index (BMI), blood sugar levels, and total cholesterol levels. This activity followed by 80 respondents whose ages range from 41 to 87 years old, 48 male and 32 female. The BMI analysis shows that 40 % of the respondents categorized as overweight and obese. Blood pressure examination found 33,75 % of the respondent has above-normal blood pressure. Respondents with normal blood sugar only 45 %, and the rest need further examination. Cholesterol levels in the high and rather high categories were found in 8.75% of respondents. These data indicate that the prevalence of risk factors for cardiovascular disease is quite large in the Demulih Village community in the adult and elderly age groups.